U.S. bound journey of migrant peoples InTransit across Dante's Inferno and Purgatory in the Americas. Issue 47 (May 2022) - Higuita, Nelson Agudelo; Suarez, Jose Antonio; Millender, Eugenia; Creighton, Elizabeth Garcia; Corbisiero, Michaele Francesco; Freites, Christian Olivo; Cordero, Jose Henao; Kousari, Arianna; Unterborn, Rebecca; Marcos, Luis A.; Henao-Martínez, Andres F.; Jhangimal, Monica; et al.
Abstract: Rapid rise of population migration is a defining feature of the 21st century due to the impact of climate change, political instability, and socioeconomic downturn. Over the last decade, an increasing number of migrant peoples travel across the Americas to reach the United States seeking asylum or cross the border undocumented in search of economic opportunities. In this journey, migrant people experience violations of their human rights, hunger, illness, violence and have limited access to medical care. In the ' Divine Comedy ', the Italian poet Dante Alighieri depicts his allegorical pilgrimage across Hell and Purgatory to reach Paradise. More than 700 years after its publication, Dante's poem speaks to the present time and the perilious journey of migrant peoples to reach safehavens. By exploring the depths and heights of the human condition, Dante's struggles resonate with the multiple barriers and the unfathomable experiences faced by migrant peoples in transit across South, Central, and North America to reach the United States. Ensuring the safety of migrant peoples across the Americas and elsewhere, and attending to their health needs during their migratory paths represent modern priorities to reduce social injustices and achieving health equity.